To prove sinA/(1-cosA) = (1+cosA)/sinA.
Proof:
we know that,
sin^2 A+cos^2 A= 1, is a trigonometric identity.
Therefore,
sin^2 A = 1- cos^2 A = (1+cosA)(1-cosA). So,
Sin^2 A /(1-cosA) = 1+cosA or
sinA/(1-cosA) = (1+cosA)/sinA.
Note:
The original problem is sinA/1-cosA = 1+cosA/sinA. This is not an identity, for,
SinA/1-cosA = 1+cosA/sinA. This means:
Put A= 0 deg. Then,
LHS = sin 0 /1 -cos0) = 1/1 - 1 = 1 -1 = 0 .
RHS= 1 + cos 0 / sin 0 = 1+1/0 = infinite.
Therefore, it is edited to read as:
Prove sinA/(1-cosA) = (1+cosA)/sinA.
No comments:
Post a Comment